Language in Teacher Education Programs at Escuela Normal Rural Ricardo Flores Magón (1929-2022): An Analysis Based on the Historical Archiv: El lenguaje en los programas de educación normal de la Escuela Normal Rural Ricardo Flores Magón (1929-2022): un análisis desde el archivo histórico (Papeles, 2025)
Introduction: This study analyzes how language has been configured as both an object of teaching and a means of professional formation in the study programs of Teacher Training Colleges (escuelas normales), through a historical analysis of the archives of the Escuela Normal Rural Ricardo Flores Magón (ENRRFM). It is guided by the research question: How has language been configured as an object of teaching and a means of formation in the study programs of Teacher Training Colleges? Methodology: Following a qualitative and interpretive approach, the research adopts Grounded Theory as its main methodology. Data were gathered through documentary analysis and semi-structured interviews, and were examined using open, axial, and selective coding to identify emerging categories. Results and Discussion: The findings show that conceptions of language have shifted from normative and prescriptive models to more critical, communicative, and sociocultural perspectives. Language is revealed as a tool for literacy, identity, and thinking, as well as a social practice embedded in community contexts. These transformations reflect ideological tensions between homogenizing policies and inclusive approaches. Conclusions: The treatment of language in teacher education programs has not been neutral, but rather a reflection of historical and political tensions. Language has become a transversal axis in teacher education, integrating knowledge, ethics, and social commitment. A historical perspective reveals its role as a political and pedagogical tool for educational transformation, particularly in contexts of linguistic and cultural diversity.
Keywords: Language; teacher training; historical archive; curriculum program